2014
DOI: 10.1111/add.12698
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of antidepressants in the treatment of adolescents and young adults with depression and substance use disorders: a systematic review and meta‐analysis

Abstract: Antidepressant medication has a small overall effect in reducing depression in young patients with combined depressive and substance-use disorders, but does not appear to improve substance use outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Meta-analysis and reviews that integrate results of clinical studies in which patients with AUD and depression were treated with ADs show drug-dependent and inconclusive results. Some findings showed that SSRIs adequately treat depressive symptomatology in individuals with AUD and depression [85][86][87], while others showed that SSRIs were not more effective than placebo in treating comorbid patients [88,89]. In relation, it has also been seen that SSRIs would not show greater effects than TCAs [90].…”
Section: Clinical Evidence Of Antidepressant Treatment Improves Deprementioning
confidence: 99%
“…Meta-analysis and reviews that integrate results of clinical studies in which patients with AUD and depression were treated with ADs show drug-dependent and inconclusive results. Some findings showed that SSRIs adequately treat depressive symptomatology in individuals with AUD and depression [85][86][87], while others showed that SSRIs were not more effective than placebo in treating comorbid patients [88,89]. In relation, it has also been seen that SSRIs would not show greater effects than TCAs [90].…”
Section: Clinical Evidence Of Antidepressant Treatment Improves Deprementioning
confidence: 99%
“…Medication assisted and physiologic therapy [90] Report of a review of studies of transcranial magnetic stimulation on addiction [62] A review outcome studies of the effectiveness of EEG Biofeedback for treatment of substance use disorder [65] Evaluated the use of transcranial magnetic stimulation on smoking cueinduced craving [91] Evaluated the use of selective serotonin reuptake inhibitors for substance use disorders.…”
Section: References Notesmentioning
confidence: 99%
“…In terms of depression, Zhou and colleagues (58) included five RCTs in a meta-analysis comparing antidepressants, namely selective serotonin reuptake inhibitors, to placebo for treatment of co-occurring unipolar depression and SUD (e.g., alcohol, cannabis, and other substances) in youth aged ≤ 25 years. Overall, antidepressant medication produced modest reductions in depressive symptoms, but improvement in substance use outcomes did not surpass the effect of placebo.…”
Section: Introductionmentioning
confidence: 99%